The Influence of The Level of Religiosity, Knowledge of The Tax Administration System and The Legitimacy of Tax Authorities on The Compliance of Taxpayers In Aceh With Tax Morale as Moderation - Mustafa Kamal; Nadirsyah Nadirsyah; Nuraini Nuraini (Publikasi Indonesia, 2023)
This study aimed at testing the influence of religiosity level, the knowledge on tax administration systems, and tax authorities legitimacy on tax compliance. The population in this study are individual and institutional tax payers registered in the Aceh Regional Office of Directorate General of Taxation. After selected through purposive sampling techniques, 400 taxpayers are selected as the sample for this research. The data analysis techniques used are multiple linear regression and moderation analysis. The results of the study revealed that the religiosity level, knowledge on tax administration systems, and tax morale influence the tax compliance. On the other hand, tax authority legitimacy do not have influence on tax compliance. However, tax morale diminished the relationship between religiosity level, knowledge on tax administration systems, tax authority legitimacy, and tax compliance.